Enhancement of physical properties of gelatin-based film by bovine serum albumin - Ahda, Mustofa; Jaswir, Irwandi; Subara, Deni (2022)
Biopolymer-based films are created from plant or animal materials such as carbohydrates and proteins. In this study, a biopolymer-based film from gelatin and Bovine Serum Albumin (BSA) was created to form a film through cross-linking interaction of both biopolymers. The synthesized biopolymer film was characterized using Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM), and Fourier Transform Infrared (FTIR) as morphological evaluation. Besides, the encapsulation efficiency of BSA-gelatin blend film was also evaluated. The coagulation process was performed using acetone carried out at 35 oC for 4 hours under stirring. The formed particles were separated from the solution using high centrifugation around 12,000 rpm for 30 min and then kept at -80 oC. Based on the FTIR spectra showed that BSA and gelatin have the same functional group such as hydroxyl (OH) and Amina I, II, and III which appear at 3278 cm-1 , 1633 cm-1 , 1542 cm-1 , and 1241 cm-1 , respectively. After linkage reaction, the gelatin-BSA interaction created more strength interaction that caused no vibration functional groups seen. It also increased glass transition temperature where the resulted melting point of gelatinbased and 70% BSA/gelatin-based films are 152.2 and 260 °C, respectively. The encapsulated BSA in the blend film reached above 90% in the BSA/gelatin ratio of 70%.